2019
DOI: 10.1186/s12909-019-1775-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life (QoL) among medical students in Saudi Arabia: a study using the WHOQOL-BREF instrument

Abstract: Background Poor Quality of Life (QoL) among medical students is associated with an unhealthy lifestyle, psychological distress, and academic failure, which could affect their care for patients in the future. This study aimed to evaluate the reliability and validity of the Arabic WHOQOL-BREF tool among Saudi medical students and to assess the effect of gender, educational level, and academic performance on their QoL. Methods This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
1
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 27 publications
(30 reference statements)
8
51
1
15
Order By: Relevance
“…Most of the validation studies revealed a four-factor structure of the WHOQOL-BREF scale [6,11,15]. Similar to studies in Australia [11] and China [12], one recent study showed that the WHOQOL-BREF tool is valid (four domains) and reliable (the Cronbach's α coefficient was over 0.7 for the questionnaire as a whole, and for all domains) for assessing quality of life among Saudi medical students [16]. In one validation study in Turkey [17], both structure and convergent validity for the WHOQOL-BREF scale were satisfactory.…”
Section: Introductionmentioning
confidence: 80%
“…Most of the validation studies revealed a four-factor structure of the WHOQOL-BREF scale [6,11,15]. Similar to studies in Australia [11] and China [12], one recent study showed that the WHOQOL-BREF tool is valid (four domains) and reliable (the Cronbach's α coefficient was over 0.7 for the questionnaire as a whole, and for all domains) for assessing quality of life among Saudi medical students [16]. In one validation study in Turkey [17], both structure and convergent validity for the WHOQOL-BREF scale were satisfactory.…”
Section: Introductionmentioning
confidence: 80%
“…A literatura mostra resultados semelhantes em estudantes da área da saúde (Enfermagem e Medicina) com valores para a percepção da QV variando de 3,7 a 4,0 e para a percepção da saúde entre 3,6 a 3,9. De acordo com os estudos, a QV foi considerada boa ou muito boa por 57 a 73% dos indivíduos e a satisfação com a saúde de 51 a 68% (CRUZ et al, 2018;GAN;YUEN LING, 2019;MALIBARY et al, 2019;MOURA et al, 2016;SAUPE et al, 2004). Porém, de acordo com os nossos resultados, deve-se considerar que 8% consideraram a QV ruim ou muito ruim e 17% se declararam muito insatisfeitos ou insatisfeitos coma própria saúde.…”
Section: Discussionunclassified
“…Os resultados mostraram que os domínios "relações sociais" e "meio ambiente" tiveram os maiores valores, por outro lado, os domínios "psicológico" e "físico" foram os mais baixos. Esses resultados foram semelhante à outros estudos envolvendo estudantes da área da saúde como Enfermagem, Medicina e Odontologia, que mostraram que o domínio "relações sociais" (ABOSHAIQAH; CRUZ, ANDRE et al, 2017;COSTA et al, 2018;MOURA et al, 2016) e "meio ambiente" (MALIBARY et al, 2019) também tiveram valores elevados. No entanto, outros estudos mostraram que os domínios "psicológico" e "físico" tiveram os maiores valores (CRUZ et al, 2018;GAN;YUEN LING, 2019).…”
Section: Discussionunclassified
See 2 more Smart Citations